2014
DOI: 10.4049/jimmunol.1301309
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 and MicroRNA-21 Promote the Expansion of Functional Myeloid-Derived Suppressor Cells

Abstract: Myeloid-derived suppressor cells (MDSC) are one of the main cell populations that negatively regulate immune responses. However, the mechanism underlying the expansion of MDSC remains unclear. Using miRNA microarray and TaqMan probe–based quantitative RT-PCR assay, we identified microRNA (miR)-155 and miR-21 as the two most upregulated miRNAs during the induction of MDSC from the bone marrow cells by GM-CSF and IL-6. High levels of miR-155 and miR-21 also were detected in bone marrow and spleen MDSC isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
162
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(174 citation statements)
references
References 52 publications
11
162
1
Order By: Relevance
“…We found that the percentage of miR-210-expressing positive cells was significantly higher on tumor-infiltrating MDSCs as compared with splenic MDSC in both B16-F10 (Fig. 1A) and 4T1 ( Although several miRNAs have been reported to regulate MDSCs function and differentiation (15,22,23), it should be noted that we did not observe any difference under hypoxia in the expression levels of miR-21, miR-155, miR-494, and miR-223 in both B16-F10 spleen Gr1 þ ( Supplementary Fig. S1E) and 4T1 spleen Gr1 þ ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 91%
“…We found that the percentage of miR-210-expressing positive cells was significantly higher on tumor-infiltrating MDSCs as compared with splenic MDSC in both B16-F10 (Fig. 1A) and 4T1 ( Although several miRNAs have been reported to regulate MDSCs function and differentiation (15,22,23), it should be noted that we did not observe any difference under hypoxia in the expression levels of miR-21, miR-155, miR-494, and miR-223 in both B16-F10 spleen Gr1 þ ( Supplementary Fig. S1E) and 4T1 spleen Gr1 þ ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 91%
“…66 Overexpression of miR-155 and miR-21 enhances the frequency of cytokineinduced MDSCs and induces the expansion of both monocytic and granulocytic MDSCs. 66 Accordingly, depletion of miR-155 and miR-21 has the opposite effect. These results demonstrate a novel miR-155/miR-21-based regulatory mechanism that modulates functional MDSC induction.…”
Section: Inflammatory Cytokines and Growth Factorsmentioning
confidence: 99%
“…STAT3 activation increases survival and proliferation of myeloid progenitor cells and regulates MDSC expansion through inducing the expression of S100A8 and S100A9 proteins [23,24]. The combination of IL-6 and GM-CSF has been identified to generate MDSCs from both human and murine immune cells [25,26]. Beyond GM-CSF and IL-6, microbial factors have been described to induce MDSCs.…”
Section: Expansionmentioning
confidence: 99%
“…Percentages of circulating G-MDSCs correlated with pulmonary function in CF patients chronically infected with P. aeruginosa. MDSCs could, therefore, represent a novel therapeutic target in CF patients, particularly in patients chronically infected with P. aeruginosa [26].…”
Section: Cystic Fibrosismentioning
confidence: 99%